Petrography, geochemistry and geochronology of igneous rocks from the Jiangnan Orogen, South China: constraints on the Early Paleozoic tectonic evolution of the South China Block - Tang, Yuanyuan; Shi, Yu; Weng, Boyin; Zhou, Yuxi; Lan, Yuanchun (Frontiers in Earth Science, 2023)
The Early Paleozoic tectonic evolution of the South China Block (SCB) remains controversial related to intracontinental orogenic and oceanic subduction processes. We present whole-rock major and trace elemental data, LA-ICP-MS zircon U-Pb age and Lu-Hf isotopic data for the Early Paleozoic igneous rocks including granodiorites from the Yuechengling pluton and volcanic breccias from the Damingshan pluton from the western segment of the Jiangnan Orogen in the SCB. LA-ICP-MS zircon U-Pb dating yielded emplacement ages for the Yuechengling S-type granitoids of 438-436 Ma and the deposited age for the Damingshan volcaniclastic rocks to be later than 451 Ma. The Yuechengling granitoids have consistent SiO2, TiO2, Fe2O3T, MgO, and P2O5 contents, higher Al2O3 contents, and Na2O + K2O values, but lower Mg# values, compared with those of the Damingshan volcaniclastic rocks. All the studied samples exhibit enrichment in LREEs and moderate negative Eu anomalies (δEu = 0.63-0.75), with negative Ba, Sr, Nb, Ta, P, and Ti anomalies, and positive Rb, Th, U, Pb, and K anomalies. The granitoids have variable CaO/Na2O ratios of 0.22-1.11, negative εHf(t) values of -11.98 to -0.90, and corresponding TDM2 ages distributed from 2.37 to 1.55 Ga. The petrographic and geochemical characteristics of the Yuechengling granitoids indicate that their parental magma was derived from a crustal meta-greywacke and meta-pelite components in the Paleoproterozoic basement, and have undergone some degree of fractional crystallization. The volcaniclastic rocks have mostly negative εHf(t) values with partially positive (-27.54 to 8.73), and zircons with negative εHf(t) values (-27.54 to -0.14) show TDM2 ages of 3.79 to 1.63 Ga. Combined with petrographic and geochemical data, we suggest that the Damingshan volcaniclastic rocks were derived from Neoarchean-Neoproterozoic crustal materials and the felsic parental magma has undergone some degree of magma mixing with mantle material, and deposited soon after a Late Ordovician volcanic eruption (later than 451 Ma). Integrated with previous studies, our new data support the intracontinental orogenic model to account for the Early Paleozoic tectonic evolution. Thus, we suggest that the Early Paleozoic tectonic setting of the SCB was intracontinental orogeny rather than oceanic subduction-collision.